Le Beautie_Saloon Sdn. Bhd. / Md Fakhruddin Md Nazri ... [et al.] - Md Nazri, Md Fakhruddin; Abdul Azias, Abdul Halim; Harun, Noor Hanis; Tahar, Khairul Azlin; Abdul Majid, Shahida (Faculty of Communication and Media Studies, 2003)
Le Beautie Saloon, is the name of our company, and we provide beauty services and also aromatherapy with natural herbs and spices. We are hopeful that you will be satisfied with our project paper we had accomplished. We also would like to say our deepest appreciation and thank you for your support and guidance throughout the project. We hope that this project paper can be used in the near future as the guidelines to our business career.